Application of Criminal Law Actors Spreading hate speech through social media based on Act Number 19 of 2016 concerning Information and Electronic Transactions (ITE) - Laode Dedi Abdulah; Siti Aisyah (Research institutions and community service Universitas Muhammadiyah Buton, 2020)
Technological developments are not only in the form of positive impacts, but also negative impacts, criminal acts of contempt or hate speech, and dissemination of information on social media aimed at inciting hatred or animosity between certain individuals and/or groups of people based on over ethnicity, religion, race and class. The purpose of this study was to determine the application of material criminal law against the perpetrators of the dissemination of hate speech through social media in decision Number 38/ Pid.Sus/2018/PN-Bau Smelling about spreading hate speech through social media. This research is a qualitative normative law research. Source of data comes from primary data in the form of legislation, secondary data and tertiary data. The results showed that (1) The application of criminal law against the perpetrators of criminal acts spreading hate speech through social media in case No. 38/Pid.Sus/2018/PN Bau, in the case of the writer who discussed this the criminal provisions of Article 45 A paragraph (2) jo. Article 28 paragraph (2) of the Law of the Republic of Indonesia Number 19 of 2016 concerning Amendments to the Law of the Republic of Indonesia Number 11 of 2008 concerning Information and Electronic Transactions. Based on the indictment, the demands of the Public Prosecutor and the court's decision; (2) Judge's Considerations in Imposing Criminal Sanctions Against Actors spreading hate speech through social media in case number 38/Pid.Sus/2018/ PN Bau based on consideration of legal facts include witness statements, defendant statements and evidence, then the judge considers juridical aspects (legal certainty), sociological value (expediency) and philosophical (justice).